Elliptic flow of heavy-flavor decay electrons in Au+Au collisions at √sNN = 27 and 54.4 GeV at RHIC - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physics letters, 2023)
We report on new measurements of elliptic flow (v2) of electrons from heavy-flavor hadron decays at mid-rapidity (|y|<0.8) in Au+Au collisions at sNN = 27 and 54.4 GeV from the STAR experiment. Heavy-flavor decay electrons (eHF) in Au+Au collisions at sNN = 54.4 GeV exhibit a non-zero v2 in the transverse momentum (pT) region of pT< 2 GeV/c with the magnitude comparable to that at sNN=200 GeV. The measured eHF v2 at 54.4 GeV is also consistent with the expectation of their parent charm hadron v2 following number-of-constituent-quark scaling as other light and strange flavor hadrons at this energy. These suggest that charm quarks gain significant collectivity through the evolution of the QCD medium and may reach local thermal equilibrium in Au+Au collisions at sNN=54.4 GeV. The measured eHF v2 in Au+Au collisions at sNN= 27 GeV is consistent with zero within large uncertainties. The energy dependence of v2 for different flavor particles (π,ϕ,D0/eHF) shows an indication of quark mass hierarchy in reaching thermalization in high-energy nuclear collisions.
Online verfügbar: 22. Juli 2023, Artikelversion: 1. August 2023
*The STAR Collaboration: M.I. Abdulhamid, I.M. Deppner, N. Herrmann, Y.H. Leung, Y. Söhngen, P.C. Weidenkaff [und 368 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Gesehen am 30.01.2024